PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN KOLABORASI SISWA PADA PEMBELAJARAN IPAS DI KELAS V SD NEGERI 1 PUJIHARJO WONOGIRI - D.A. Siwi; Wijayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) model on the collaboration skills of grade V students in learning Natural and Social Sciences (IPAS) at SD Negeri 1 Pujiharjo Wonogiri. Data collection methods were carried out by observation, tests, questionnaires, and documentation. The population in this study were all fifth grade students at SD Negeri 1 Pujiharjo Wonogiri, totaling 25 people. The research used quantitative methods with a pre-experimental design One Group Pretest-Posttest Design. The sample of this study was 25 fifth grade students with total sampling technique. The results were analyzed using paired sample t-test, which previously conducted Normality test as a prerequisite test with the help of SPSS 26. The results showed a significant difference between pretest and posttest scores (sig. = 0.018), as well as between conventional learning questionnaire results and PjBL model (sig. = 0.001), both <0.5. This finding proves that the application of the PjBL model can affect students' collaboration skills in IPAS learning.